Nanoparticle-coated elastic microparticles and surfactant-promoted methods of making and using the same

The preparation of polyurethane particles with narrow particle size distribution and regular shape through melt emulsification technology solves the problem of poor flowability and filling efficiency of powder particles in three-dimensional printing, and achieves printing effects with high mechanical and structural integrity and low porosity.

CN112457652BActive Publication Date: 2025-04-29XEROX CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202010900344.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2020-08-31
Publication Date
2025-04-29
Estimated Expiration
2040-08-31

AI Technical Summary

Technical Problem

In the existing three-dimensional printing technology, the fluidity and filling efficiency of thermoplastic polymer powder particles are poor, resulting in weak voids and weak structure in printed items.

Method used

Polyurethane particles with narrow particle size distribution and regular shape were prepared by melt emulsification technology, and powder flowability and consolidation properties were improved using nanoparticles and sulfonate surfactants.

Benefits of technology

High mechanical and structural integrity is achieved during the three-dimensional printing process, reducing porosity, and improving powder flowability and filling efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112457652B_ABST
    Figure CN112457652B_ABST
Patent Text Reader

Abstract

The present invention is entitled "Nanoparticle-coated elastic microparticles and surfactant-promoted methods of making and using the same". When nanoparticles and sulfonate surfactants are included as emulsion stabilizers, melt emulsification can be used to form elastic microparticles within a narrow particle size range. Such a process can include combining a polyurethane polymer, a sulfonate surfactant, and nanoparticles with a carrier fluid at a heated temperature at or above the melting point or softening temperature of the polyurethane polymer, applying sufficient shear at the heated temperature in the presence of the nanoparticles to disperse the polyurethane polymer in the carrier fluid in the form of liquefied droplets, cooling the carrier fluid at least until the elastic microparticles are in a solidified state, and separating the elastic microparticles from the carrier fluid. The polyurethane polymer defines the core and outer surface of the elastic microparticle, and the nanoparticles are associated with the outer surface. The elastic microparticles can have a span of about 0.9 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Three-dimensional (3D) printing (also known as additive manufacturing) is a rapidly growing field of technology. Although 3D printing has traditionally been used for rapid prototyping activities, the technology is increasingly being used to produce commercial and industrial objects that may have structural and mechanical tolerances that are very different from those of rapid prototypes.

[0002] Three-dimensional printing operates by depositing either 1) small droplets or streams of molten or solidifiable material or 2) powder particles in precise deposition locations for subsequent consolidation into larger items, which may have any number of complex shapes. The larger item may be referred to herein as a "consolidated body". Such deposition and consolidation processes are typically performed under computer control to provide a layer-by-layer buildup of the larger item. In a specific example, a laser may be used to perform consolidation of powder particles in a three-dimensional printing system to facilitate selective laser sintering (SLS). Incomplete interlayer fusion during selective laser sintering may create structural weak points, which may be problematic for printing items with tight structural and mechanical tolerances.

[0003] Powder particles that can be used for 3D printing include those containing thermoplastic polymers (including thermoplastic elastomers), metals, and other solidifiable substances. Although a wide variety of thermoplastic polymers are known, relatively few thermoplastic polymers have properties suitable for use in current 3D printing technology, especially when using powder bed fusion (PBF) and other additive manufacturing techniques such as selective laser sintering (SLS), electron beam melting (EBM), binder jetting, and multi-jet melting (MJF) to promote particle consolidation. In the SLS printing method, energy from a high-power laser is used to consolidate the powder particles together. Typical thermoplastic polymers suitable for 3D printing include those having a clear melting point and a recrystallization point about 30°C-50°C lower than the melting point. This temperature difference allows more efficient coalescence between adjacent polymer layers, thereby promoting improved structural and mechanical integrity. Thermoplastic polymers that have these properties and have shown some successful applications in the 3D printing process include, for example, crystalline polyamides, polyurethanes, and polyether block amides.

[0004] In order to achieve good printing performance using powder particles (especially polymer powder particles), the powder particles need to maintain good flow characteristics in the solid state. The flow characteristics can be evaluated, for example, by measuring the fraction of powder particles in the sample that can pass through a standard sieve of a specified size and / or measuring the angle of repose. A high fraction of sievable powder particles can indicate that the powder particles exist in the form of non-agglomerated, essentially separate particles, which can be a feature of the ready-to-use powder flow. In contrast, a lower value of the angle of repose can be a feature of the ready-to-use powder flow. The relatively narrow particle size distribution in the sample and the regularity of the particle shape can also help promote good powder flow properties. The Hausner ratio can also indicate the powder flow properties of the sample.

[0005] Commercial powder particles are usually obtained by cryogenic grinding or precipitation processes, which can produce irregular particle shapes and wide particle size distributions. Irregular particle shapes can lead to poor powder flow properties during three-dimensional printing. In addition, powder particles with extensive shape irregularities (especially those obtained from current commercial processes) can bring poor filling efficiency after deposition during three-dimensional printing, thereby forming gaps in the printed article due to the powder particles not being tightly packed together during deposition and consolidation. Wide particle size distribution may be problematic in this regard. Although poor powder flow properties can be solved to a certain extent by dry mixing with fillers and flow aids, these technologies may have limited effectiveness for softer polymer materials (such as elastomers) due to particle agglomeration. In addition, fillers and flow aids may have little effect on improving the poor filling efficiency of irregularly shaped powder particles.

[0006] Melt emulsification (also referred to herein as melt emulsification blending) is another technique for forming powder particles of thermoplastic polymers, as described in U.S. Pat. No. 4,863,646, which is incorporated herein by reference in its entirety. In the melt emulsification process, a thermoplastic polymer is dispersed in a carrier fluid in which the polymer has no solubility or only minimal solubility above the melting point or softening temperature of the polymer. Once the melting point or softening temperature has been exceeded in the presence of sufficient shear, liquefied polymer droplets can be formed as an immiscible phase in the carrier fluid. After the liquefied polymer droplets are cooled to below the melting point or softening temperature, thermoplastic polymer powder particles having a substantially spherical shape can be formed. Unfortunately, thermoplastic polymer powder particles formed by conventional melt emulsification processes tend to have a wide particle size distribution, making the powder particles undesirably suitable for three-dimensional printing processes. In addition, the range of thermoplastic polymers that have been processed into powder particles by melt emulsification techniques to date is relatively limited, and only some of these processed thermoplastic polymers are thermoplastic polymers suitable for three-dimensional printing.

[0007] Powder particles of thermoplastic polymers may also be obtained by dispersion polymerization techniques using steric stabilizers to promote spherical particle formation as described in US Pat. No. 5,859,075, incorporated herein by reference. The powder particles obtained in this process may have similar problems as those noted above for melt emulsification.

[0008] Three-dimensional printing using elastic particles (such as polyurethane particles) has only been relatively little studied. U.S. Patent Application Publication 2017 / 0129177, incorporated herein by reference, describes a three-dimensional printing process using polyurethane particles prepared from bulk polyurethane ground with silica cryogenically. U.S. Patent Application Publication 2015 / 0152214, incorporated herein by reference, describes a three-dimensional printing process using polyurethane particles prepared from mechanically ground and sieved polyurethane. As discussed above, such ground powder particles may not be suitable for three-dimensional printing processes. International Patent Application Publication 2015 / 109143 describes thermoplastic polyurethanes that are particularly suitable for solid free-form manufacturing processes (such as selective laser sintering). Thermoplastic polyurethanes have specific melting enthalpies and crystallization temperatures, which can be changed by the specific selection and amount of synthons used to synthesize thermoplastic polyurethanes. Summary of the invention

[0009] The present disclosure relates generally to thermoplastic polymer powder particles, and more particularly to elastomeric powder particles comprising thermoplastic polyurethane polymers, their preparation using melt emulsification, and their uses.

[0010] Some aspects of the present disclosure may include a composition comprising elastic microparticles. The composition comprises: a plurality of elastic microparticles, the plurality of elastic microparticles comprising a polyurethane polymer and a plurality of nanoparticles, the polyurethane polymer defining a core and an outer surface of the elastic microparticles, and the plurality of nanoparticles associated with the outer surface; wherein the elastic microparticles have a D50 in the range of about 1 μm to about 130 μm, wherein the size span is about 0.9 or less.

[0011] Some aspects of the present disclosure may include a three-dimensional printing method using a composition containing elastic particles. The three-dimensional printing method includes: depositing the composition of the present disclosure in a specified shape; and once deposited, heating at least a portion of the elastic particles to promote consolidation of the elastic particles and form a consolidated body; wherein the consolidated body is formed layer by layer and has a porosity of about 3.5% or less after consolidation.

[0012] Some aspects of the present disclosure may include a method for forming elastic microparticles using melt emulsification. The method includes: combining a polyurethane polymer, a sulfonate surfactant, and nanoparticles with a carrier fluid at a heated temperature at or above the melting point or softening temperature of the polyurethane polymer; wherein the polyurethane polymer and the carrier fluid are substantially immiscible at the heated temperature; applying sufficient shear at the heated temperature in the presence of the sulfonate surfactant and the nanoparticles to disperse the polyurethane polymer in the carrier fluid in the form of liquefied droplets; after the liquefied droplets have been formed, cooling the carrier fluid to at least a temperature at which an elastic microparticle is in the form of a solidified state, the elastic microparticle comprising a polyurethane polymer and a plurality of nanoparticles, the polyurethane polymer defining a core and an outer surface of the elastic microparticle and the plurality of nanoparticles associated with the outer surface; wherein the elastic microparticle has a D50 in the range of about 1 μm to about 130 μm, wherein the size span is about 0.9 or less; and separating the elastic microparticle from the carrier fluid. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The following drawings are included to illustrate certain aspects of the disclosure and should not be construed as exclusive embodiments. The disclosed subject matter is capable of considerable modification, alteration, combination, and equivalents in form and function, as will occur to those of ordinary skill in the art having the benefit of this disclosure.

[0014] Figure 1 is a flow chart of a non-limiting exemplary method for preparing elastic microparticles according to the present disclosure.

[0015] Figure 2 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 1 at a magnification of 150X is shown.

[0016] Figure 3 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 1 is shown.

[0017] Figure 4 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 2 at a magnification of 150X is shown.

[0018] Figure 5A and Figure 5B Exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Comparative Example 2 at various magnifications are shown.

[0019] Figure 6 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 2 is shown.

[0020] Figure 7An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 3 at a 100X magnification is shown.

[0021] Figure 8 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 3 is shown.

[0022] Fig. 9 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 4 at a 100X magnification is shown.

[0023] Fig.10 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 4 is shown.

[0024] Fig.11 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 1 at 300X magnification is shown.

[0025] Fig.12 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 1 is shown.

[0026] Fig.13 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 2 at 150X magnification is shown.

[0027] Fig.14 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 2 is shown.

[0028] Fig.15 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 3 at 150X magnification is shown.

[0029] Fig.16 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 3 is shown.

[0030] Fig.17 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 4 at 150X magnification is shown.

[0031] Fig.18A and Fig.18B Exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Example 4 at various magnifications are shown.

[0032] Fig.19 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 4 is shown.

[0033] Fig. 20An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 5 at 150X magnification is shown.

[0034] Fig.21 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 5 is shown.

[0035] Fig. 22 Exemplary particle size distribution graphs of thermoplastic polyurethane microparticles obtained from Comparative Examples 1 and 4 and Example 3 are shown.

[0036] Fig.23 An optical image of the printed product obtained in Example 6 using thermoplastic polyurethane microparticles specified in entry 5 of Table 3 (40% laser power) is shown. DETAILED DESCRIPTION

[0037] The present disclosure relates generally to thermoplastic polymer powder particles, and more particularly to elastomeric powder particles comprising thermoplastic polyurethane polymers, their preparation using melt emulsification, and their uses.

[0038] As discussed above, only a relatively limited number of thermoplastic polymer types are suitable for 3D printing. Further complicating the issue, commercially available powder particles of thermoplastic polymers are often not well suited for 3D printing due to their irregular particle shape and wide particle size distribution, each of which can lead to poor powder flow and deposition characteristics. Additionally, the irregular particle shape and wide particle size distribution can lead to poor packing efficiency after deposition, which can lead to the formation of voids in the printed object and a corresponding lack of structural and mechanical integrity.

[0039] Advantageously, the present disclosure provides thermoplastic powder particles that are more suitable for three-dimensional printing, specifically, elastic particles comprising polyurethane polymers. That is, the elastic particles of the present disclosure can be formed in a certain way by melt emulsification so that they have excellent shape regularity (substantially spherical) and narrow particle size distribution. In addition, the elastic particles of the present disclosure can be easily sieved and show low angle of repose values, which can bring good powder flow characteristics. Although it is advantageous in three-dimensional printing, the elastic particles disclosed herein can also be advantageous in other applications, because they have shape regularity and narrow particle size distribution.

[0040] The elastic particles of the present disclosure with these characteristics can be prepared by an improved melt emulsification process. Different from conventional melt emulsification processes, sufficient nanoparticles (particularly oxide nanoparticles) can be mixed in a melt emulsification medium (carrier fluid) with a polyurethane polymer or similar thermoplastic polymer so that a uniform coating of nanoparticles is produced on the elastic particles when the particles solidify from the melt emulsification medium after cooling. Silica nanoparticles (particularly hydrophobic functionalized silica nanoparticles) belong to oxide nanoparticles suitable for the disclosure herein. Nanoparticles (particularly oxide nanoparticles) can act as emulsion stabilizers to form coatings on elastic particles during melt emulsification, thereby improving powder flow characteristics and / or changing particle size distribution in a desired manner. Advantageously, nanoparticle coatings can bring powder flow characteristics that are more suitable for three-dimensional printing processes. Good powder flow characteristics can also bring advantages in other applications (such as powder paints and coatings). More details about the melt emulsification process of the present disclosure are provided below.

[0041] Another advantage of the present disclosure is that the nanoparticles do not have to be dry-mixed with the elastic microparticles in a separate blending process, thereby defining two discrete microparticle processing steps: 1) microparticle formation and 2) microparticle modification by dry blending. In contrast, conventional melt emulsification processes can blend silica as a flow aid with the microparticles after preparation. Not only is the separate blending operation an inefficient process, but poor uniformity of coverage and non-robust adhesion to the microparticles can occur. Including nanoparticles in the melt emulsification medium according to the present disclosure can solve these problems and provide related advantages. Because the dry blending process does not incorporate a robust nanoparticle coating onto the surface of the elastic microparticles, different microparticle properties, such as performance differences during three-dimensional printing, can be produced. Therefore, the nanoparticle coating in the present disclosure can have a stabilizing effect on the elastic microparticles, thereby preventing or minimizing aggregation or agglomeration of the elastic microparticles during heating, cooling, processing and drying.

[0042] It is also surprising and advantageous that the incorporation of a surfactant, specifically a sulfonate surfactant (anionic surfactant), into the molten emulsification medium can make the particle size distribution even narrower than that obtained by the nanoparticles alone. Without being bound by theory or mechanism, it is believed that a variety of interactions occur between the polyurethane polymer, the nanoparticles and the sulfonate surfactant to cause the particle size distribution to narrow. The extent to which the particle size distribution narrows can be associated with the amount of sulfonate surfactant present. Further narrowing of the particle size distribution in the presence of a sulfonate surfactant can provide additional advantages, such as increasing the amount of elastic particles that can pass through the sieve after production and improving flow characteristics. In fact, using the disclosure of this article, the fraction of elastic particles that can pass through the sieve can exceed 90%, compared to about 80% or less of the sieveable material in the absence of a sulfonate surfactant. Advantageously, any elastic particles that cannot pass through the sieve can be recycled in a subsequent melt emulsification process. If desired, the carrier fluid and washing solvent can be similarly recycled. Therefore, the present disclosure can provide improved process economics by reducing material waste during sieving.

[0043] The elastic particles disclosed herein can bring additional advantages in the three-dimensional printing process. Due to their shape regularity and narrow particle size distribution, the elastic particles disclosed herein can have a lower incidence of void formation after consolidation to form a printed object. The lower incidence of void formation can bring higher mechanical and structural integrity than can be achieved using commercial elastic particles currently. In addition, the elastic particles disclosed herein can be consolidated by laser sintering at a lower laser power than the laser power possible when using elastic particles with poorer shape regularity and wider particle size distribution, mainly by minimizing the incidence of larger elastic particles or their agglomerates, which can require higher laser power to promote sintering. When consolidating the elastic particles disclosed herein, a lower incidence of powder formation can be achieved on the back of the printed layer, which can be contrasted with the behavior observed in the absence of sulfonate surfactants.

[0044] The terms used in this specification and claims have their plain and ordinary meanings except as modified in the following paragraphs.

[0045] As used herein, the term "immiscible" refers to a mixture of components that, when combined, form two or more phases that have less than 5 weight percent solubility in each other at ambient pressure and room temperature or the melting points of the components if they are solid at room temperature. For example, polyethylene oxide having a molecular weight of 10,000 g / mol is solid at room temperature and has a melting point of 65° C. Thus, if a material that is liquid at room temperature and the polyethylene oxide have less than 5 weight percent solubility in each other at 65° C., the polyethylene oxide is immiscible with the material.

[0046] As used herein, the term "polyurethane" refers to the polymer reaction product between a diisocyanate, a polyol, and an optional chain extender.

[0047] As used herein, the term "elastomer" refers to a copolymer comprising a crystalline "hard" segment and an amorphous "soft" segment. For example, in the case of a polyurethane, the crystalline segment may include a portion of a polyurethane having carbamate functional groups and optional chain extender groups, and the soft segment may include a polyol.

[0048] As used herein, the term "nanoparticle" refers to particulate material having a particle size ranging from about 1 nm to about 500 nm.

[0049] As used herein, the term "oxide" refers to both metal oxides and non-metal oxides. For the purposes of this disclosure, silicon is considered a metal.

[0050] As used herein, the term "oxide nanoparticles" refers to particulate materials having a particle size ranging from about 1 nm to about 500 nm and comprising a metal oxide or a non-metal oxide.

[0051] As used herein, the terms "associated," "associated," and grammatical variations thereof between an emulsion stabilizer and a surface refer to chemical bonding and / or physical adhesion of the emulsion stabilizer to the surface. Without being limited by theory, it is believed that the association between the polymers described herein and the emulsion stabilizer is primarily physical adhesion via hydrogen bonding and / or other mechanisms. However, chemical bonding may occur to some extent.

[0052] As used herein, the term "embedded" with respect to nanoparticles and polymer particle surfaces means that the nanoparticles extend at least partially into the surface such that the polymer contacts the nanoparticles to a greater extent than would occur if the nanoparticles were simply laid down on the polymer particle surface.

[0053] As used herein, the term "D10" refers to the diameter at which 10% of the sample (on a volume basis unless otherwise specified) consists of particles having a diameter less than the stated diameter value. As used herein, the term "D50" refers to the diameter at which 50% of the sample (on a volume basis unless otherwise specified) consists of particles having a diameter less than the stated diameter value. D50 may also be referred to as the "average particle size". As used herein, the term "D90" refers to the diameter at which 90% of the sample (on a volume basis unless otherwise specified) consists of particles having a diameter less than the stated diameter value.

[0054] As used herein, the terms "diameter span," "size span," and "span" refer to the width of the particle size distribution and can be calculated by the relationship (D90-D10) / D50 (again, unless otherwise indicated, each D value is based on volume).

[0055] As used herein, the term "shear" refers to stirring or similar processes that cause mechanical agitation in a fluid.

[0056] As used herein, the term "aspect ratio" refers to the length divided by the width, wherein the length is greater than the width.

[0057] As used herein, the term "embedded" with respect to the nanoparticles and the elastomeric microparticle surface means that the nanoparticles extend at least partially into the surface such that the polymer contacts the nanoparticles to a greater extent than would occur if the nanoparticles were simply laid down on the elastomeric microparticle surface.

[0058] As used herein, unless otherwise specified, the viscosity of the carrier fluid is the kinematic viscosity at 25° C. and is measured in accordance with ASTM D445-19. For commercially purchased carrier fluids (e.g., PDMS oil), the kinematic viscosity data cited herein are provided by the manufacturer, whether measured in accordance with the aforementioned ASTM or another standard measurement technique.

[0059] Figure 1 1 is a flow chart of a non-limiting exemplary method 100 for preparing elastic microparticles according to the present disclosure. As shown, at 108, a polyurethane polymer 102, a carrier fluid 104, and an emulsion stabilizer 106 are combined to produce a mixture 110. The polyurethane polymer 102, the carrier fluid 104, and the emulsion stabilizer 106 can be combined in any order at 108, and the process of combining at 108 includes mixing and / or heating. In a specific example, the carrier fluid 104 can be heated to above the melting point or softening temperature of the polyurethane polymer 102 before the polyurethane polymer 102 and the emulsion stabilizer 106 are combined therewith. The emulsion stabilizer 106 can contain multiple nanoparticles, specifically multiple oxide nanoparticles and sulfonate surfactants, in any combination or ratio in the present disclosure. In the emulsion stabilizer 106, one or more types of nanoparticles and one or more types of sulfonate surfactants can exist in any combination and ratio.

[0060] Heating to above the melting point or softening temperature of the polyurethane polymer 102 can be performed at any temperature below the decomposition temperature or boiling point of any component in the molten emulsion. In a non-limiting example, heating can be performed at a temperature of about 1°C to about 50°C, or about 1°C to about 25°C, or about 5°C to about 30°C, or about 20°C to about 50°C higher than the melting point or softening temperature of the polyurethane polymer 102. In the disclosure herein, a 10°C / min ramp rate and cooling rate can be used to determine the melting point by ASTME794-06 (2018). Unless otherwise specified, the softening temperature or softening point of the polymer is determined by ASTM D6090-17. The softening temperature can be measured using a cup-ball apparatus available from Mettler-Toledo, using a 0.50 gram sample at a heating rate of 1°C / min. The melting point or softening temperature in the present disclosure can be in the range of about 50°C to about 400°C.

[0061] The polyurethane polymer 102 may have a glass transition temperature (derived from ASTM E1356-08 (2014) using a 10°C / min ramp rate and cooling rate) of about -50°C to about 400°C (or about -50°C to about 0°C, or about -25°C to about 50°C, or about 0°C to about 150°C, or about 100°C to about 250°C, or about 150°C to about 300°C, or about 200°C to about 400°C).

[0062] The mixture 110 is then processed at 112 by applying sufficient shear at a temperature greater than the melting point or softening temperature of the polyurethane polymer 102 to produce liquefied droplets of the polyurethane polymer 102, thereby forming a molten emulsion 114. Without being limited by theory, it is believed that increasing shear can reduce the size of the liquefied droplets in the carrier fluid 104, all other factors being equal. It should be understood that there may be diminishing returns to increasing shear and subsequently reducing droplet size at a certain point, and / or damage to the droplet contents may occur at higher shear rates that may reduce the quality of microparticles produced therefrom. Sulfonate surfactants can help stabilize the liquefied droplets by reducing coalescence with other liquefied droplets, thereby helping to maintain a narrower particle size distribution after the elastic microparticles are formed.

[0063] Examples of mixing devices for preparing the molten emulsion 114 include, but are not limited to, extruders (eg, continuous extruders, batch extruders, etc.), stirred reactors, mixers, reactors with in-line homogenizer systems, and the like, and devices derived therefrom.

[0064] In non-limiting examples, the liquefied droplets may have a particle size of about 1 μm to about 1,000 μm, or about 1 μm to about 500 μm, or about 1 μm to about 150 μm, or about 1 μm to about 130 μm, or about 1 μm to about 100 μm, or about 10 μm to about 100 μm, or about 20 μm to about 80 μm, or about 20 μm to about 50 μm, or about 50 μm to about 90 μm. Particle size measurements can be made by analyzing optical images or using the built-in software of a Malvern Mastersizer 3000Aero S instrument that uses light scattering technology for particle size measurements.

[0065] For light scattering techniques, the Quality Audit Standards (QAS4002) can be used. TM Glass microbead control samples ranging in diameter from 15 μm to 150 μm were purchased from Malvern Analytical Ltd. Samples can be analyzed as dry powders dispersed in air using the dry powder dispersion module of the Mastersizer 3000Aero S. Particle size can be derived from a plot of bulk density versus size using the instrument software.

[0066] The molten emulsion 114 is then cooled at 116 to solidify the liquefied droplets into polyurethane polymer particles (i.e., polyurethane microparticles in a solidified state, also referred to herein as "elastic microparticles"). The cooling rate may be in the range of about 100°C / second to about 10°C / hour or about 10°C / second to about 10°C / hour, including any cooling rate therebetween. Shearing may be interrupted during cooling, or may be maintained at the same rate or at different rates during cooling. The cooled mixture 118 may then be processed at 120 to separate the polyurethane microparticles 122 from other components 124 (e.g., carrier fluid 104, excess emulsion stabilizer 106, etc.). Washing, filtering, etc. may be performed at this stage to further purify the polyurethane microparticles 122. The polyurethane microparticles 122 include at least a portion of the polyurethane polymer 102 and the emulsion stabilizer 106 coating the outer surface of the polyurethane microparticles 122. Once the polyurethane microparticles have been formed, nanoparticles and optionally sulfonate surfactants may be associated with the outer surface. The emulsion stabilizer 106 or a portion thereof may be deposited on the polyurethane microparticles 122 as a uniform coating. In some cases, which may depend on non-limiting factors such as temperature (including cooling rate), type of polyurethane polymer 102, and type and size of emulsion stabilizer 106, nanoparticles of emulsion stabilizer 106 may be at least partially embedded within the outer surface of polyurethane microparticles 122 during association with the outer surface of the polyurethane microparticles 122. Even if embedding does not occur, at least the nanoparticles within the emulsion stabilizer 106 may remain robustly associated with the polyurethane microparticles 122 to facilitate their further use. In contrast, dry mixing already formed polyurethane microparticles (e.g., formed by cryogenic grinding or precipitation processes) with a flow aid (such as silica nanoparticles) does not produce a robust, uniform coating of the flow aid on the polyurethane microparticles.

[0067] In the foregoing, the polyurethane polymer 102 and the carrier fluid 104 are selected such that these components are immiscible or substantially immiscible (<5 wt % solubility), particularly <1 wt % solubility, at various processing temperatures (e.g., from room temperature to temperatures at which liquefied droplets form and remain in two or more phases).

[0068] After the polyurethane particles 122 are separated from the other components 124, further processing 126 of the polyurethane particles 122 may be performed. In a non-limiting example, the further processing 126 may include, for example, screening the polyurethane particles 122 and / or blending the polyurethane particles 122 with other substances to form processed polyurethane particles 128. The processed polyurethane particles 128 may be formulated for a desired application, such as three-dimensional printing in a non-limiting example.

[0069] Thus, the melt emulsification process of the present disclosure may include: combining an elastic polyurethane, a sulfonate surfactant, and nanoparticles with a carrier fluid at a heated temperature at or above the melting point or softening temperature of the polyurethane polymer; applying sufficient shear at the heated temperature in the presence of the sulfonate surfactant and the nanoparticles to disperse the polyurethane polymer in the carrier fluid in the form of liquefied droplets; after the liquefied droplets have been formed, cooling the carrier fluid to at least a temperature at which the elastic particles are in the form of a solidified state; and separating the elastic particles from the carrier fluid. In such a process, the polyurethane polymer and the carrier fluid are substantially immiscible at the heated temperature. The elastic particles include a polyurethane polymer and a plurality of nanoparticles, wherein the polyurethane polymer defines a core and an outer surface of the elastic particles, and the plurality of nanoparticles are associated with the outer surface. In a specific example, the elastic particles may have a D50 in the range of about 1 μm to about 130 μm, wherein the size span is about 0.9 or less.

[0070] The elastic particles may have a viscosity of about 0.3 g / cm 3 To about 0.8g / cm 3 , or about 0.3g / cm 3 To about 0.6g / cm 3 , or about 0.4g / cm 3 To about 0.7g / cm 3 , or about 0.5g / cm 3 To about 0.6g / cm 3 , or about 0.5g / cm 3 To about 0.8g / cm 3 The bulk density.

[0071] In a particular example of the present disclosure, a shear sufficient to form a liquefied droplet can be applied by stirring the carrier fluid. In a non-limiting example, the stirring rate can be in the range of about 50 revs / min (RPM) to about 1500RPM, or about 250RPM to about 1000RPM, or about 225RPM to about 500RPM. The stirring rate when melting the polyurethane polymer can be the same or different from the stirring rate used after the liquefied droplet has been formed. The liquefied droplet can be stirred in a stirring time of about 30 seconds to about 18 hours or longer, or about 1 minute to about 180 minutes, or about 1 minute to about 60 minutes, or about 5 minutes to about 6 minutes, or about 5 minutes to about 30 minutes, or about 10 minutes to about 30 minutes, or about 30 minutes to about 60 minutes.

[0072] The polyurethane polymers suitable for use in the present disclosure are considered to be not particularly limited. In particular examples, suitable polyurethane polymers may have properties consistent with use in three-dimensional printing, including those having soft segments containing polyethers, polyesters, or any combination thereof. Other polyurethanes that are more suitable for other applications may be selected as needed.

[0073] Although various embodiments herein relate to elastic particles comprising polyurethane (particularly elastic polyurethane), it should be recognized that other thermoplastic elastomers can be used to similarly implement the disclosure herein. Other thermoplastic elastomers (natural or synthetic) that can be suitable for use in any composition and method disclosed herein generally belong to one of six categories: styrenic block copolymers, thermoplastic polyolefin elastomers, thermoplastic vulcanizates (also referred to as elastomer alloys), thermoplastic copolyesters, and thermoplastic polyamides (generally block copolymers comprising polyamide blocks). Examples of other suitable thermoplastic elastomers can be found in the following literature: Handbook of Thermoplastic Elastomers, 2nd edition, edited by BMW Walker and CP Rader, Van Nostrand Reinhold, New York, 1988. Examples of other suitable thermoplastic elastomers for use in the present disclosure include, but are not limited to, elastomeric polyamides, copolymers comprising polyether blocks and polyamide blocks (PEBA or polyether block amide), methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, siloxanes, etc. Any specific disclosure herein involving polyurethanes (including, but not limited to, loading ranges, processing temperature ranges, etc.) may be implemented in a similar manner using any of the foregoing or similar thermoplastic elastomers.

[0074] Suitable elastic styrenic block copolymers may include at least one block selected from isoprene, isobutylene, butene, ethylene / butylene, ethylene-propylene and ethylene-ethylene / propylene. More specific examples of elastic styrenic block copolymers include, but are not limited to, poly(styrene-ethylene / butylene), poly(styrene-ethylene / butylene-styrene), poly(styrene-ethylene / propylene), poly(styrene-ethylene / propylene-styrene), poly(styrene-ethylene / propylene-styrene-ethylene-propylene), poly(styrene-butadiene-styrene), poly(styrene-butylene-butadiene-styrene), the like and any combination thereof.

[0075] Examples of suitable polyamide elastomers include, but are not limited to, polyesteramides, polyetheresteramides, polycarbonate-esteramides, and polyether-block-amide elastomers.

[0076] The loading (concentration) of the polyurethane polymer in the carrier fluid can vary over a wide range. The loading in the carrier fluid can play at least some role in determining the properties of the elastic microparticles obtained after the liquefied droplet solidifies. In a non-limiting example, the loading of the polyurethane polymer in the carrier fluid can be in the range of about 1% by weight to about 99% by weight relative to the weight of the carrier fluid. In a more specific example, the loading of the polyurethane polymer can be in the range of about 5% by weight to about 75% by weight, or about 10% by weight to about 60% by weight, or about 20% by weight to about 50% by weight, or about 20% by weight to about 30% by weight, or about 30% by weight to about 40% by weight, or about 40% by weight to about 50% by weight, or about 50% by weight to about 60% by weight. The polyurethane polymer can be present in an amount ranging from about 5 wt % to about 60 wt %, or from about 5 wt % to about 25 wt %, or from about 10 wt % to about 30 wt %, or from about 20 wt % to about 45 wt %, or from about 25 wt % to about 50 wt %, or from about 40 wt % to about 60 wt %, relative to the combined amount of the polyurethane polymer and the carrier fluid (solid loading).

[0077] Various nanoparticles, particularly oxide nanoparticles, can be suitable for forming the elastic microparticles of the present disclosure. Oxide nanoparticles suitable for use in the disclosure include, for example, silicon dioxide nanoparticles, titanium dioxide nanoparticles, zirconium oxide nanoparticles, aluminum oxide nanoparticles, iron oxide nanoparticles, copper oxide nanoparticles, tin oxide nanoparticles, boron oxide nanoparticles, cerium oxide nanoparticles, thallium oxide nanoparticles, tungsten oxide nanoparticles, or any combination thereof. The term "oxide" also encompasses mixed oxides such as aluminosilicates, borosilicates, and aluminoborosilicates. Oxide nanoparticles can be hydrophilic or hydrophobic, which may be natural for the nanoparticles or produced by surface treatment of the particles. For example, silicon dioxide nanoparticles with hydrophobic surface treatment (such as dimethylsilyl, trimethylsilyl, etc.) can be formed by reacting hydrophilic surface hydroxyls. Hydrophobic functionalized oxide nanoparticles may be particularly desirable in the methods and compositions of the present disclosure. Non-functionalized oxide nanoparticles may also be suitable for use.

[0078] Silica nanoparticles, particularly pyrogenic silica nanoparticles with hydrophobic functionalization thereon, may be particularly suitable for use in this disclosure, since a variety of functionalized silicas are available, wherein the type and particle size of the hydrophobic functionalization vary. Silazane and silane hydrophobic functionalizations are simple hydrophobic functionalizations that can be used in the present disclosure. Therefore, the multiple oxide nanoparticles used in this disclosure may comprise silica nanoparticles, specifically hydrophobically functionalized silica nanoparticles, or may be substantially composed of silica nanoparticles. When another type of oxide or non-oxide nanoparticles can transmit properties that cannot be obtained when using separate silica nanoparticles to elastic microparticles or articles formed therefrom, silica nanoparticles may be used in conjunction with the oxide nanoparticles or non-oxide nanoparticles of this another type.

[0079] Carbon black is another type of nanoparticle that can be present as an emulsion stabilizer in the compositions and methods disclosed herein. Various grades of carbon black are familiar to those of ordinary skill in the art, and any of these grades of carbon black can be used herein. Other nanoparticles that can absorb infrared radiation can similarly be used.

[0080] Polymer nanoparticles are another type of nanoparticles that can be present in the form of emulsion stabilizers in the present disclosure. Suitable polymer nanoparticles can include one or more polymers that are thermosetting and / or crosslinked so that they do not melt when processed by melt emulsification according to the present disclosure. High molecular weight thermoplastic polymers with high melting points or decomposition points can similarly include suitable polymer nanoparticle emulsion stabilizers.

[0081] When forming elastic microparticles according to the present disclosure, the loading (concentration) and particle size of the silica nanoparticles can vary widely. The loading and particle size of the silica nanoparticles can play at least some role in determining the properties of the elastic microparticles obtained after solidification of the liquefied droplets.

[0082] In non-limiting examples, the loading capacity of the silicon dioxide nanoparticles in the carrier fluid can be in the range of about 0.01 wt % to about 10 wt % or about 0.05 wt % to about 10 wt % or about 0.05 wt % to about 5 wt % relative to the weight of the polyurethane polymer. In a more specific example, the loading capacity of the silicon dioxide nanoparticles can be in the range of about 0.1 wt % to about 5 wt % or about 0.1 wt % to about 2 wt % or about 0.25 wt % to about 1.5 wt % or about 0.2 wt % to about 1.0 wt % or about 0.25 wt % to about 1 wt % or about 0.25 wt % to about 0.5 wt %. Other types of nanoparticles, particularly oxide nanoparticles, can be used with similar loading capacity scopes.

[0083] In a non-limiting example, the particle size of the silicon dioxide nanoparticles can be in the range of about 1nm to about 100nm. In some cases, the particle size of the silicon dioxide nanoparticles can be up to 500nm. In a more specific example, the particle size of the silicon dioxide nanoparticles can be in the range of about 5nm to about 75nm, or about 5nm to about 50nm, or about 5nm to about 10nm, or about 10nm to about 20nm, or about 20nm to about 30nm, or about 30nm to about 40nm, or about 40nm to about 50nm, or about 50nm to about 60nm. Other types of nanoparticles, particularly oxide nanoparticles, can be used with similar particle size ranges.

[0084] Nanoparticles (particularly silica nanoparticles and other oxide nanoparticles) may have a diameter of about 10 m 2 / g to about 500m 2 / g, or about 10m 2 / g to about 150m 2 / g, or about 25m 2 / μ to about 100m 2 / g, or about 100m 2 / g to about 250m 2 / g, or about 250m 2 / g to about 500m 2 / g of BET surface area.

[0085] Specific silica nanoparticles suitable for the disclosure herein may be hydrophobically functionalized. Such hydrophobic functionalization may make the silica nanoparticles less compatible with water than non-functionalized silica nanoparticles. In addition, hydrophobic functionalization may improve the dispersibility of silica nanoparticles in a carrier fluid, which may be highly hydrophobic. Hydrophobic functionalization may be non-covalently or covalently attached to the surface of the silica nanoparticles. Covalent attachment may be performed, for example, by functionalization of surface hydroxyls on the surface of the silica nanoparticles. In a non-limiting example, hexamethyldisilazane may be used to treat the silica nanoparticles to provide hydrophobically modified covalent functionalization. Commercially available hydrophobically functionalized silica nanoparticles include, for example, Aerosil RX50 (Evonik, average particle size = 40nm) and Aerosil R812S (Evonik, average particle size = 7nm).

[0086] Non-functionalized silica nanoparticles may also be used as emulsion stabilizers in the present disclosure.

[0087] Similarly, the loading (concentration) and type of sulfonate surfactant may play at least some role in determining the properties of the elastic microparticles obtained after solidification of the liquefied droplets. In a non-limiting example, the loading of the sulfonate surfactant in the carrier fluid may be in the range of about 0.01 wt % to about 10 wt %, or about 0.1 wt % to about 10 wt %, or about 0.5 wt % to about 5 wt %, or about 1 wt % to about 7 wt %, or about 1 wt % to about 5 wt %, or about 2.5 wt % to about 5 wt %, or about 1 wt % to about 3 wt % relative to the polyurethane polymer.

[0088] Exemplary sulfonate surfactants that may be suitable for use in the present disclosure include, for example, docusate sodium (sodium dioctyl sulfosuccinate) and similar sulfosuccinates, branched alkyl (e.g., C 12 ) diphenyl ether disulfonic acid sodium salt, alkylbenzene sulfonic acid sodium salt (such as sodium dodecylbenzene sulfonate and other benzene sulfonates with linear alkyl groups), perfluorosulfonate surfactants, α-olefin sulfonic acid sodium salt, lignin sulfate, and any combination thereof.

[0089] Other anionic surfactants can be similarly used in the disclosure herein to form elastic microparticles having one or more of the following characteristics: a D50 within the particle size range disclosed above, a size span of about 0.9 or less, and / or a fraction of elastic microparticles in a sample that can pass through a sieve of a specified size of about 90% or greater. Other anionic surfactants that can be used according to the disclosure herein include, for example, alkyl carboxylates, alkyl sulfates, alkyl ether sulfates, coconut sulfates, glycerol sulfates, aryl sulfates, phosphates, phosphites, and phosphonates, and any combination thereof. For example, an alkyl sulfate surfactant can provide a D50 of about 1 μm to about 130 μm, and a high yield of elastic microparticles that can pass through a sieve, but has a span greater than that obtained using a sulfonate surfactant under similar processing conditions.

[0090] After forming the elastic microparticles according to the disclosure herein, at least a portion of the nanoparticles (such as silica nanoparticles) can be disposed on the outer surface of the elastic microparticles in the form of a coating. At least a portion of the sulfonate surfactant can also be associated with the outer surface. The coating can be substantially uniformly disposed on the outer surface. As used herein with respect to the coating, the term "substantially uniform" refers to a uniform coating thickness in the surface positions (particularly the entire outer surface) covered by the nanoparticles. The coating coverage of the elastic microparticles containing nanoparticles and / or surfactants can be in the range of about 5% to about 100% of the microparticle surface area, or about 5% to about 25%, or about 20% to about 50%, or about 40% to about 70%, or about 50% to about 80%, or about 60% to about 90%, or about 70% to about 100%. The coverage can be determined by image analysis of SEM micrographs. The elastic microparticles of the present disclosure can contain about 90% by weight to about 99.5% by weight of polyurethane polymer.

[0091] Carrier fluids suitable for use in the present disclosure include those in which the polyurethane polymer is substantially immiscible with the carrier fluid, the carrier fluid having a boiling point exceeding the melting point or softening temperature of the polyurethane polymer, and the carrier fluid having sufficient viscosity to form liquefied droplets of substantially spherical shape after the polyurethane polymer has melted therein. Suitable carrier fluids may include, for example, silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, alkyl-terminated polyethylene glycol (e.g., C1-C4 terminal alkyl groups, such as tetraethylene glycol dimethyl ether (TDG)), paraffin, liquid petrolatum, vison oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, parleam oil, grape seed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, almond oil, castor oil, avocado oil, jojoba oil, olive oil, corn germ oil, esters of lanolic acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, polysiloxanes modified with fatty acids, polysiloxanes modified with fatty alcohols, polysiloxanes modified with polyoxyalkylenes, and the like, and any combination thereof.

[0092] Suitable carrier fluids may have a viscosity of about 0.6 g / cm 3 To about 1.5g / cm 3 The density of the polyurethane polymer may be about 0.7 g / cm 3 To about 1.7g / cm 3 wherein the polyurethane polymer has a similar, lower, or higher density than the density of the carrier fluid.

[0093] Particularly suitable silicone oils are polysiloxanes. Exemplary silicone oils suitable for use in the present disclosure include, for example, polydimethylsiloxane (PDMS), methylphenyl polysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenyl polysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenyl polysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenyl polysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenyl polysiloxane, and the like, and any combination thereof.

[0094] In a non-limiting example, the carrier fluid and the polyurethane polymer may be heated at a temperature of about 200° C. or higher. A suitable heating temperature may be selected based on the melting point or softening temperature of the polyurethane polymer and the boiling point of the carrier fluid. The cooling rate after the formation of the liquefied polymer droplets may be varied as desired. In some cases, cooling may be performed by dissipating heat to the surrounding environment at an inherent (uncontrolled) rate after the heating is interrupted. In other cases, cooling at a controlled rate may be employed (e.g., by gradually reducing the heating temperature and / or using jacket temperature control to increase or decrease the cooling rate).

[0095] The carrier fluid (such as polysiloxane, including PDMS) can have a viscosity of about 1,000 cSt to about 150,000 cSt, or about 1,000 cSt to about 60,000 cSt, or about 40,000 cSt to about 100,000 cSt, or about 75,000 cSt to about 150,000 cSt at 25° C. The viscosity of the carrier fluid can be obtained from commercial suppliers or, if desired, can be measured by techniques known to those of ordinary skill in the art.

[0096] The elastic particles may be separated from the carrier fluid by any of a variety of known separation techniques. Any of gravity settling and filtration, decanting, centrifugation, etc. may be used to separate the elastic particles from the carrier fluid. The elastic particles may be washed with a solvent in which the carrier fluid is soluble and the elastic particles are not soluble during the separation process. Additionally, a solvent in which the carrier fluid is soluble and the elastic particles are not soluble may be mixed with the carrier fluid and the elastic particles prior to initially separating the elastic particles from the carrier fluid.

[0097] Suitable solvents for washing the elastic microparticles or mixing with the carrier fluid may include, but are not limited to, aromatic hydrocarbons (e.g., toluene and / or xylene), aliphatic hydrocarbons (e.g., heptane, n-hexane and / or n-octane), cyclic hydrocarbons (e.g., cyclopentane, cyclohexane and / or cyclooctane), ethers (e.g., diethyl ether, tetrahydrofuran, diisopropyl ether and / or dioxane), halogenated hydrocarbons (e.g., ethylene dichloride, trichloroethane, dichloromethane, chloroform and / or carbon tetrachloride), alcohols (e.g., methanol, ethanol, isopropanol and / or n-propanol), ketones (e.g., methyl ethyl ketone and / or acetone); esters (e.g., ethyl acetate, etc.), water, etc., and any combination thereof.

[0098] After washing the elastomeric particles, any of heating, vacuum drying, air drying, or any combination thereof may be performed. If desired, additional washing and / or pyrolysis may be employed to remove surfactant from the outer surface.

[0099] Despite washing the elastomeric particles with a solvent, a limited amount of carrier fluid may remain in some cases. In a non-limiting example, any of the elastomeric particles of the present disclosure may include a non-zero amount of up to about 5% by weight of a carrier fluid that remains associated with a plurality of elastomeric particles. The carrier fluid may be associated with the outer surface of the elastomeric particles and / or trapped in voids or cavities within the elastomeric particles. Up to 5% by volume of voids may be present in the elastomeric particles, wherein the voids may be filled or unfilled.

[0100] At least most of the elastic microparticles obtained according to the disclosure herein can be substantially spherical in shape. More typically, about 90% or more, or about 95% or more, or about 99% or more of the elastic microparticles prepared by melt emulsification according to the present disclosure can be substantially spherical in shape. In other non-limiting examples, the elastic microparticles of the present disclosure can have a sphericity (roundness) of about 0.9 or more, including about 0.90 to about 1.0, or about 0.93 to about 0.99, or about 0.95 to about 0.99, or about 0.97 to about 0.99, or about 0.98 to 1.0. The sphericity (roundness) can be measured using a Sysmex FPIA-2100 flow particle image analyzer. In order to determine the roundness, an optical microscopic image is taken of the microparticles. The circumference (P) and area (A) of the microparticles in the plane of the microscopic image are calculated (for example, using a SYSMEX FPIA 3000 particle shape and size analyzer, available from Malvern Instruments). The circularity of the microparticles is C EA / P, where C EA It is the circumference of a circle whose area is equal to the area (A) of the actual particle.

[0101] The elastic microparticles of the present disclosure may have an angle of repose of about 25° to about 45°, or about 25° to about 35°, or about 30° to about 40°, or about 35° to about 45°. The angle of repose may be determined using ASTM D6393-14, "Standard Test Method for Bulk Solids Characterized by Carr Indices," using a Hosokawa Micron Powder Characterization Tester PT-R.

[0102] In addition, the elastic microparticles formed according to the disclosure herein may have a plurality of silicon dioxide nanoparticles or other nanoparticles at least partially embedded in the outer surface defined by the polyurethane polymer. When silicon dioxide nanoparticles or other nanoparticles are at least partially embedded in the outer surface, a part of the nanoparticle structure may be located in a pit or depression in the outer surface, thereby making it more difficult to remove nanoparticles from the surface. It should be understood that even when substantial embedding does not occur, suitable functionalized nanoparticles (such as hydrophobic functionalized silicon dioxide nanoparticles) may also non-covalently associate (e.g., using van der Waals type interactions) to promote nanoparticles to remain on the outer surface.

[0103] Surprisingly, the elastic particles formed according to the present disclosure may include one or more elongated structures on the outer surface of the elastic particles. The one or more elongated structures may have an aspect ratio of at least about 10. When present, silica nanoparticles or other nanoparticles may be disposed on the surface of the one or more elongated structures. The surface coverage density of the nanoparticles on the one or more elongated structures may be the same or different than the surface coverage density directly on the outer surface of the elastic particles.

[0104] The elastic particles separated from the carrier fluid according to the above disclosure can be further processed to make the elastic particles suitable for the intended application. In one example, the elastic particles can pass through a sieve or similar structure having an effective screening size greater than the average particle size of the elastic particles. For example, an exemplary screening size for processing elastic particles suitable for three-dimensional printing may have an effective screening size of about 150 μm. When referring to screening, the hole / sieve size is described in accordance with the American Standard Sieve (ASTM E11-17). Other screening sizes (either larger or smaller) may be more suitable for elastic particles designated for other applications. Screening can remove larger particles that may have been formed during the melt emulsification process, and / or remove agglomerated particles that may have poor flow characteristics. In general, a sieve with an effective screening size in the range of about 10 μm to about 250 μm can be used.

[0105] In addition, the elastic particles passing through the screen or similar structure can be mixed with one or more additional components, such as a flow aid, a filler or other material intended to customize the properties of the elastic particles for the intended application. The mixing of the additional components with the elastic particles can be carried out by dry mixing techniques. Suitable examples of flow aids (e.g., carbon black, graphite, silicon dioxide, etc.) and similar materials are familiar to those of ordinary skill in the art.

[0106] In view of the foregoing, the present disclosure also provides a composition comprising powder particles with a coating, the coating comprising nanoparticles, particularly oxide nanoparticles. The composition may include a plurality of elastic particles, the plurality of elastic particles comprising a polyurethane polymer and a plurality of nanoparticles, specifically oxide nanoparticles, wherein the polyurethane polymer defines the core and outer surface of the elastic particles, and the plurality of nanoparticles are associated with the outer surface. Optionally, a sulfonate surfactant or a similar anionic surfactant may also be associated with the outer surface. In a specific example, the elastic particles may have a D50 in the range of about 1 μm to about 130 μm, wherein the size span is about 0.9 or less. Elastic particles with such D50 and span can be prepared in the presence of a sulfonate surfactant. In the presence of an alternative type of anionic surfactant, elastic particles with similar D50 values ​​but higher spans can be prepared.

[0107] As discussed herein, the nanoparticles on the outer surface of the elastic microparticles can be metallic nanoparticles or non-metallic nanoparticles, particularly silica nanoparticles or other oxide nanoparticles. Silica nanoparticles with hydrophobic functionalization (either alone or in combination with other types of nanoparticles) can be particularly beneficial as emulsion stabilizers associated with the outer surface of the elastic microparticles.

[0108] Based on the turbidity measurement of the elastic microparticles formed in the absence of anionic surfactants, about 80%-90% of the available nanoparticles (such as silica nanoparticles) become associated with the elastic microparticles. Since the loading of nanoparticles is measured relative to the polyurethane polymer, the amount of nanoparticles associated with the elastic microparticles can be about 80%-90% of the nanoparticle loading used when forming the elastic microparticles. Therefore, for a nanoparticle loading of 0.25% by weight, the corresponding amount of nanoparticles associated with the elastic microparticles can be about 0.2% by weight to about 0.225% by weight, and for a nanoparticle loading of 1.0% by weight, the corresponding amount of nanoparticles associated with the elastic microparticles can be about 0.8% by weight to about 0.9% by weight. For higher or lower nanoparticle loadings in the carrier fluid, higher or lower amounts of nanoparticles associated with the elastic microparticles can be achieved.

[0109] The size of the elastic particles that can be prepared according to the disclosure herein is considered to be not particularly limited, but can be about 150 μm or less, or 125 μm or less, or 100 μm or less to facilitate use in various applications (such as three-dimensional printing). Particularly suitable elastic particles can have a D50 in the range of about 1 μm size to about 130 μm size, as described above. Particle size measurement can be performed using a Malvern Mastersizer 3000Aero S instrument. Various factors (as non-limiting examples, such as the size, type and loading of nanoparticles, the size and loading of sulfonate surfactants, shear rate, heating temperature, cooling rate, carrier fluid and its viscosity, and the specific polyurethane used) can also affect the size and / or particle size distribution of the elastic particles obtained according to the present disclosure. One or more of these factors can also determine whether the sphericity of the elastic particles and / or the carrier fluid are retained in the elastic particles in a non-zero amount.

[0110] Depending on the conditions under which the elastic particles are prepared, at least a portion of the elastic particles may include one or more elongated structures located on the outer surface of the elastic particles. The one or more elongated structures may have an aspect ratio of at least about 10.

[0111] In yet other non-limiting embodiments, the compositions disclosed herein may further comprise glidants or additional components that may facilitate the use of the elastic microparticles in a desired application. Suitable examples of each component are familiar to those of ordinary skill in the art.

[0112] In certain applications, the compositions disclosed herein can be used in three-dimensional printing processes, particularly those that employ selective laser sintering to promote particle consolidation. The elastic particles of the present disclosure can exhibit properties superior to those of elastic particles having irregular shapes or wider particle distributions, such as those commercially available. In a non-limiting example, the elastic particles of the present disclosure can consolidate at lower laser powers and provide reduced void formation in articles prepared by three-dimensional printing.

[0113] The three-dimensional printing process of the present disclosure may include: depositing the composition of the present disclosure containing elastic particles onto a surface in a specified shape, and once deposited, heating at least a portion of the elastic particles to promote consolidation of the elastic particles and form a consolidated body (article). The consolidated body may have a porosity of about 5% or less, or about 3% or less, or about 1% or less after consolidation. In a specific example, the heating and consolidation of the elastic particles can be performed by using a three-dimensional printing device, such as those using powder bed fusion (PBF), selective laser sintering (SLS), selective heat sintering (SHS), selective laser melting (SLM), electron beam melting (EBM), binder jetting, and multi-jet melting (MJF).

[0114] Any of the elastomeric particles disclosed herein may be formulated as compositions suitable for three-dimensional printing. The selection of a particular composition and type of elastomeric particles may be based on various factors, such as, but not limited to, the laser power used for selective laser sintering, the type of article to be prepared, and the conditions of intended use of the article.

[0115] Examples of articles that may be formed using three-dimensional printing in accordance with the present disclosure are considered to be without particular limitation, and may include, for example, containers (e.g., for food, beverages, cosmetics, personal care compositions, pharmaceuticals, etc.), shoe soles, toys, furniture parts, decorative household items, plastic gears, screws, nuts, bolts, cable ties, medical supplies, prostheses, orthopedic implants, preparation of artifacts to aid learning in education, 3D anatomical models to aid surgery, robotics, biomedical devices (orthotics), household appliances, dentistry, automotive and aircraft / aerospace components, electronic devices, sporting goods, and the like.

[0116] Other applications of the disclosed elastomeric particles may include, but are not limited to, use as fillers in paints and powder coatings, inkjet materials, and electrophotographic toners, etc. In some cases, the elastomeric particles may have other preferred properties, such as diameter and span, that may be useful for such other applications.

[0117] Embodiments disclosed herein include:

[0118] A. A composition comprising elastic microparticles. The composition comprises: a plurality of elastic microparticles comprising a polyurethane polymer and a plurality of nanoparticles, the polyurethane polymer defining a core and an outer surface of the elastic microparticles, and the plurality of nanoparticles associated with the outer surface; wherein the elastic microparticles have a D50 in the range of about 1 μm to about 130 μm, wherein the size span is about 0.9 or less.

[0119] A1. A composition comprising elastic microparticles. The composition comprises: a plurality of elastic microparticles, the plurality of elastic microparticles comprising a thermoplastic elastomer and a plurality of nanoparticles, the thermoplastic elastomer defining a core and an outer surface of the elastic microparticles, and the plurality of nanoparticles associated with the outer surface; wherein the elastic microparticles have a D50 in the range of about 1 μm to about 130 μm, wherein the size span is about 0.9 or less.

[0120] B. A three-dimensional printing method using a composition containing elastic microparticles. The three-dimensional printing method includes: depositing the composition of the present disclosure in a specified shape; and once deposited, heating at least a portion of the elastic microparticles to promote consolidation of the elastic microparticles and form a consolidated body; wherein the consolidated body is formed layer by layer and has a porosity of about 3.5% or less after consolidation.

[0121] C. A method for forming elastic microparticles using melt emulsification. The method comprises: combining a polyurethane polymer, a sulfonate surfactant, and nanoparticles with a carrier fluid at a heated temperature at or above the melting point or softening temperature of the polyurethane polymer; wherein the polyurethane polymer and the carrier fluid are substantially immiscible at the heated temperature; applying sufficient shear at the heated temperature in the presence of the sulfonate surfactant and the nanoparticles to disperse the polyurethane polymer in the carrier fluid in the form of liquefied droplets; after the liquefied droplets have been formed, cooling the carrier fluid to at least a temperature at which an elastic microparticle is in the form of a solidified state, the elastic microparticle comprising a polyurethane polymer and a plurality of nanoparticles, the polyurethane polymer defining a core and an outer surface of the elastic microparticle and the plurality of nanoparticles associated with the outer surface; wherein the elastic microparticle has a D50 in the range of about 1 μm to about 130 μm, wherein the size span is about 0.9 or less; and separating the elastic microparticle from the carrier fluid.

[0122] Each of embodiments A, A1, B and C may have one or more of the following additional elements in any combination:

[0123] Element 1: wherein the plurality of nanoparticles comprises or consists essentially of a plurality of oxide nanoparticles.

[0124] Element 1A: wherein the plurality of oxide nanoparticles comprises or consists essentially of silicon dioxide nanoparticles.

[0125] Element 1B: wherein the plurality of nanoparticles comprises or consists essentially of carbon black or polymer nanoparticles.

[0126] Element 2: wherein the plurality of oxide nanoparticles are hydrophobically functionalized silica nanoparticles.

[0127] Element 3: wherein the silica nanoparticles have a D50 in the range of about 5 nm to about 50 nm.

[0128] Element 4: wherein the silica nanoparticles are at least partially embedded in the outer surface.

[0129] Element 5: wherein the silica nanoparticles are substantially uniformly coated on the outer surface.

[0130] Element 6: wherein the composition further comprises a sulfonate surfactant.

[0131] Element 7: wherein at least a portion of the sulfonate surfactant is associated with an outer surface.

[0132] Element 8: wherein the composition further comprises a non-zero amount of about 5 weight % of silicone oil in the plurality of elastic particles.

[0133] Element 9: wherein at least a majority of the plurality of elastic particles are substantially spherical in shape.

[0134] Element 10: wherein at least a portion of the plurality of elastic particles comprises one or more elongated structures located on an outer surface, the one or more elongated structures having an aspect ratio of at least about 10.

[0135] Element 11: wherein the composition is deposited and the elastic particles are consolidated using a three-dimensional printing device.

[0136] Element 12: wherein the heating is performed by selective laser sintering.

[0137] Element 13: wherein the plurality of nanoparticles remain associated with the solid body

[0138] Element 14: wherein the elastic microparticles further comprise a sulfonate surfactant.

[0139] Element 15: wherein at least a portion of the sulfonate surfactant is associated with an outer surface.

[0140] Element 16: wherein a non-zero amount of up to about 5 weight percent of a carrier fluid remains associated with the plurality of elastomeric particles.

[0141] Element 17: wherein the carrier fluid has a viscosity at 25°C in the range of about 1,000 cSt to about 150,000 cSt.

[0142] Element 18: wherein the carrier fluid comprises silicone oil.

[0143] Element 19: wherein at least a portion of the sulfonate surfactant is associated with a plurality of elastic microparticles.

[0144] Element 20: wherein at least a portion of the sulfonate surfactant is associated with an outer surface.

[0145] Element 21: wherein the solid loading in the carrier fluid is in the range of about 20 wt % to about 50 wt %.

[0146] Element 22: wherein the loading amount of the nanoparticles in the carrier fluid is in the range of about 0.1 wt % to about 5 wt % relative to the polyurethane polymer.

[0147] Element 23: wherein the method further comprises: passing at least a portion of the elastic particles through a screen; and optionally, formulating the elastic particles that passed through the screen with one or more additional components.

[0148] As non-limiting examples, exemplary combinations suitable for A, B and C include, but are not limited to: A and C, including 1, 1A, 1B or 2 and 3; 1, 1A, 1B or 2 and 4; 1, 1A, 1B or 2 and 5; 1, 1A, 1B or 2 and 6; 1, 1A, 1B or 2, 6 and 7; 1, 1A, 1B or 2 and 9; 3 and 4; 3 and 5; 3 and 6; 3, 6 and 7; 3 and 9; 4 and 5; 4 and 6; 4, 6 and 7; 5 and 6; 5-7; 4 and 9; 5 and 9; 6 and 9; and 6, 7 and 9. Exemplary combinations suitable for B include any one of 1-9 and any one of 17-23; 17 and 18; 17 and 19; 17, 19 and 20; 17 and 21; 17 and 22; 17 and 23; 18 and 19; 18 and 20; 18 and 21; 18 and 22; 18 and 23; 19 and 20; 19 and 21; 19 and 22; 19 and 23; 21 and 22; 21 and 23; and 22 and 23. Exemplary combinations suitable for B include any one of 1-9 and 11; any one of 1-9, 11 and 12; 11 and 12; 11 and 13; 12 and 13; 11-13; 11 and 14; 11, 14 and 15; 12 and 14; and 12, 14 and 15.

[0149] Terms of this Disclosure

[0150] Clause 1: A composition comprising:

[0151] a plurality of elastomeric particles, the plurality of elastomeric particles comprising a polyurethane polymer and a plurality of nanoparticles, the polyurethane polymer defining a core and an outer surface of the elastomeric particles, and the plurality of nanoparticles associated with the outer surface;

[0152] The elastic particles have a D50 in the range of about 1 μm to about 130 μm, with a size span of about 0.9 or less.

[0153] Item 2: The composition of Item 1, wherein the plurality of nanoparticles comprises or consists essentially of a plurality of oxide nanoparticles.

[0154] Clause 2A: The composition of Clause 2, wherein the plurality of oxide nanoparticles comprises or consists essentially of silicon dioxide nanoparticles.

[0155] Clause 2B: The composition of Clause 1, wherein the plurality of nanoparticles comprises or consists essentially of carbon black or polymer nanoparticles.

[0156] Item 3: The composition of Item 2A, wherein the plurality of oxide nanoparticles are hydrophobically functionalized silica nanoparticles.

[0157] Item 4: The composition of Item 3, wherein the silica nanoparticles have a D50 in a range from about 5 nm to about 50 nm.

[0158] Clause 5: The composition of Clause 3, wherein the silica nanoparticles are at least partially embedded in the outer surface.

[0159] Clause 6: The method of Clause 2A, wherein the silica nanoparticles are substantially uniformly coated on the outer surface.

[0160] Item 7: The composition of Item 2, further comprising a sulfonate surfactant.

[0161] Item 8: The composition of Item 7, wherein at least a portion of the sulfonate surfactant is associated with the exterior surface.

[0162] Clause 9: The composition according to clause 1, further comprising:

[0163] A non-zero amount of about 5 weight percent silicone oil comprises the plurality of elastomeric particles.

[0164] Item 10: The composition of Item 1, wherein at least a majority of the plurality of elastic particles are substantially spherical in shape.

[0165] Item 11: The composition of Item 1, wherein at least a portion of the plurality of elastomeric particles comprises one or more elongated structures on an outer surface, the one or more elongated structures having an aspect ratio of at least about 10.

[0166] Clause 12: A method comprising:

[0167] depositing the composition according to clause 1 in a specified shape; and

[0168] Once deposited, heating at least a portion of the elastomeric particles to promote consolidation of the elastomeric particles and form a consolidated body;

[0169] The consolidated body is formed layer by layer and has a porosity of about 3.5% or less after consolidation.

[0170] Item 13: The method of Item 12, wherein the composition is deposited and the elastic particles are consolidated using a three-dimensional printing device.

[0171] Item 14: The method of Item 13, wherein the heating is performed by selective laser sintering.

[0172] Clause 15: The method of Clause 12, wherein the plurality of nanoparticles remain associated with the consolidated body.

[0173] Clause 16: The method of Clause 12, wherein the plurality of nanoparticles comprises or consists essentially of a plurality of oxide nanoparticles.

[0174] Clause 16A: The method of Clause 16, wherein the plurality of oxide nanoparticles comprises or consists essentially of silicon dioxide nanoparticles.

[0175] Clause 16B: The method of Clause 16, wherein the plurality of oxide nanoparticles are hydrophobically functionalized silica nanoparticles.

[0176] Clause 16C: The method of Clause 12, wherein the plurality of nanoparticles comprises or consists essentially of carbon black or polymer nanoparticles.

[0177] Clause 17: The method of Clause 12, wherein the elastomeric microparticles further comprise a sulfonate surfactant.

[0178] Clause 18: The composition of Clause 17, wherein at least a portion of the sulfonate surfactant is associated with the outer surface.

[0179] Clause 19: A method comprising:

[0180] combining the polyurethane polymer, sulfonate surfactant, and nanoparticles with a carrier fluid at a heated temperature at or above the melting point or softening temperature of the polyurethane polymer;

[0181] wherein the polyurethane polymer and the carrier fluid are substantially immiscible at the heated temperature;

[0182] applying sufficient shear at the heated temperature in the presence of the sulfonate surfactant and the nanoparticles to disperse the polyurethane polymer in the carrier fluid as liquefied droplets;

[0183] After the liquefied droplets have been formed, cooling the carrier fluid to at least a temperature at which the elastomeric microparticles are in the form of a solidified state, the elastomeric microparticles comprising a polyurethane polymer defining a core and an outer surface of the elastomeric microparticles and the plurality of nanoparticles associated with the outer surface;

[0184] wherein the elastic particles have a D50 in the range of about 1 μm to about 130 μm, with a size span of about 0.9 or less; and

[0185] The elastic particles are separated from the carrier fluid.

[0186] Clause 20: The method of Clause 19, wherein the plurality of nanoparticles comprises or consists essentially of a plurality of oxide nanoparticles.

[0187] Clause 20A: The method of Clause 20, wherein the plurality of oxide nanoparticles comprises or consists essentially of silicon dioxide nanoparticles.

[0188] Item 21: The method of Item 20, wherein the plurality of oxide nanoparticles are hydrophobically functionalized silica nanoparticles.

[0189] Clause 21A: The method of Clause 19, wherein the plurality of nanoparticles comprises or consists essentially of carbon black or polymer nanoparticles.

[0190] Item 22: The method of Item 21, wherein the silica nanoparticles have a D50 in a range from about 5 nm to about 50 nm.

[0191] Clause 23: The method of Clause 21, wherein the silica nanoparticles are at least partially embedded in the outer surface.

[0192] Clause 24: The method of Clause 21, wherein the silica nanoparticles are substantially uniformly coated on the outer surface.

[0193] Clause 25: The method of Clause 19, wherein a non-zero amount to about 5 weight percent of a carrier fluid remains associated with the plurality of elastomeric particles.

[0194] Clause 26: The method of Clause 19, wherein at least a majority of the plurality of elastic particles are substantially spherical in shape.

[0195] Clause 27: The method of Clause 19, wherein the carrier fluid has a viscosity in a range of about 1,000 cSt to about 150,000 cSt at 25°C.

[0196] Clause 28: The method of clause 27, wherein the carrier fluid comprises silicone oil.

[0197] Clause 29: The method of Clause 19, wherein at least a portion of the sulfonate surfactant is associated with the plurality of elastomeric microparticles.

[0198] Clause 30: The method of Clause 29, wherein at least a portion of the sulfonate surfactant is associated with the outer surface.

[0199] Item 31: The method of Item 19, wherein the solid loading in the carrier fluid is in a range from about 20 wt% to about 50 wt%.

[0200] Item 32: The method of Item 19, wherein the loading of nanoparticles in the carrier fluid is in a range from about 0.1 wt % to about 5 wt % relative to the polyurethane polymer.

[0201] Clause 33: The method of Clause 19, wherein at least a portion of the plurality of elastomeric particles comprises one or more elongated structures on an outer surface, the one or more elongated structures having an aspect ratio of at least about 10.

[0202] Clause 34: The method according to clause 19, further comprising:

[0203] passing at least a portion of the elastomeric particles through a screen; and

[0204] Optionally, the elastomeric particles that pass through the screen are formulated using one or more additional components.

[0205] In order to facilitate a better understanding of the embodiments of the present invention, the following examples of preferred or representative embodiments are given. The following examples should in no way be construed as limiting or defining the scope of the present invention.

[0206] Example

[0207] In the following examples, the powder flow of polyurethane particles is characterized by sieving and angle of repose measurement. The sieving yield of polyurethane particles is determined in the following manner: a certain amount of polyurethane particles is exposed to a 150 μm U.S. standard sieve (ASTM E11) and the mass fraction of the particles passing through the sieve relative to the total amount of polyurethane particles is determined. The sieve is manually used in the absence of specific conditions of force duration. ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices" is used to perform angle of repose measurement using Hosokawa Micron Powder Characterization Tester PT-R.

[0208] The average particle size (D50), D10 and D90 were measured using a Malvern Mastersizer 3000Aero S particle size analyzer. Optical images were obtained using a Keyence VHX-2000 digital microscope and software version 2.3.5.1 for particle size analysis (system version 1.93). The average particle size was also obtained by processing the optical images.

[0209] Comparative Example 1: 160 g of polydimethylsiloxane (PSF-30000, Clearco) was added to a 500 mL glass reactor. The reactor was set to a stirring rate of 350 rpm using an overhead stirrer, and the temperature was raised to 190° C. Further heated to 200° C., 40 g of thermoplastic polyurethane pellets were added to the stirring polydimethylsiloxane. The thermoplastic polyurethane was poly[4,4′-methylenebis(phenyl isocyanate)-alternating-1,4-butanediol / di(propylene glycol) / polycaprolactone] (Sigma-Aldrich). Once the thermoplastic polyurethane pellets were fully combined with the polydimethylsiloxane, the stirring rate was increased to 500 rpm and the temperature was maintained at 200° C. for 60 minutes. Afterwards, stirring was stopped and the resulting slurry was allowed to cool to room temperature. The slurry was washed four times with heptane, and thermoplastic polyurethane microparticles were obtained after vacuum filtration.

[0210] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Figure 2 An exemplary optical microscopic image at 150X magnification of the thermoplastic polyurethane microparticles obtained in Comparative Example 1 is shown. The average particle size was 97.1 μm and a broad particle size distribution (span = 1.239) was obtained. Figure 3 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 1 is shown.

[0211] Comparative Example 2: 320 g of polydimethylsiloxane (PSF-30000, Clearco) and 0.25 wt % of fumed silica microparticles functionalized with hexamethyldisilazane (Aerosil RX50 from Evonik, 35 ± 10 m 2 / g BET surface area and 40nm average particle size). The reactor is set to a stirring rate of 200rpm using an overhead stirrer, and the temperature is raised to 190°C. Further heated to 200°C, 80g of thermoplastic polyurethane pellets are now added to the polydimethylsiloxane being stirred. In this case, the thermoplastic polyurethane is ELASTOLLAN1190A, which is a polyether polyurethane elastomer purchased from BASF. Once the thermoplastic polyurethane pellets are fully combined with the polydimethylsiloxane, the stirring rate is increased to 500rpm and the temperature is maintained at 200°C for 60 minutes. Afterwards, stirring is stopped and the resulting slurry is allowed to cool to room temperature. The slurry is washed four times with hexane, and thermoplastic polyurethane microparticles are obtained after vacuum filtration.

[0212] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Figure 4 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Comparative Example 2 at 150X magnification is shown. The average particle size was 95.6 μm and a broad particle size distribution was obtained (span = 0.892). The angle of repose was 29.9°. Figure 5A and Figure 5B Exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Comparative Example 2 at various magnifications are shown. Figure 6 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 2 is shown.

[0213] Comparative Example 3: Comparative Example 1 was repeated except that 1.0 wt % of poly[dimethylsiloxane-co-[3-(2-(2-hydroxyethoxy)ethoxy)propylmethylsiloxane] surfactant was mixed with the PDMS before heating to the processing temperature. Figure 7 An exemplary optical microscopic image at 100X magnification is shown of the thermoplastic polyurethane microparticles obtained in Comparative Example 3. The average particle size was 123 μm and a broad particle size distribution (span = 0.977) was obtained. Figure 8 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 3 is shown.

[0214] Comparative Example 4: Comparative Example 1 was repeated except that 2.5 wt% SPAN 80 (sorbitan maleate nonionic surfactant) was mixed with the PDMS before heating to the processing temperature. Fig. 9 An exemplary optical microscopic image at 100X magnification is shown of the thermoplastic polyurethane microparticles obtained in Comparative Example 4. The average particle size was 139 μm and a broad particle size distribution (span = 0.811) was obtained. Fig.10 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 4 is shown.

[0215] Example 1: Comparative Example 1 was repeated, except that before heating to the processing temperature, hexamethyldisilazane (Aerosil RX50 from Evonik, 35±10 m 2 0.25 wt % fumed silica microparticles functionalized with 1.0 wt % sodium dodecyl sulfate (SDS) were mixed with PDMS. Fig.11 An exemplary optical microscopic image at 300X magnification of the thermoplastic polyurethane microparticles obtained in Example 1 is shown. The average particle size was 26.8 μm and a broad particle size distribution was obtained (span = 1.251). Fig.12 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 1 is shown.

[0216] Example 2: Comparative Example 1 was repeated except that 0.25 wt% fumed silica microparticles functionalized with hexamethyldisilazane (Aerosil RX50 from Evonik, 35±10 m 2 / g BET surface area and 40 nm average particle size) and 2.5 wt % docusate sodium (sodium 1,4-bis(2-ethylhexyloxy)-1,4-dioxobutane-2-sulfonate, also known as sodium dioctyl sulfosuccinate) in combination with polydimethylsiloxane.

[0217] After separation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.13 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 2 at 150X magnification is shown. The average particle size was 31.5 μm and a relatively narrow particle size distribution was obtained (span = 0.859). The angle of repose was 38.2°. Fig.14 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 2 is shown.

[0218] Example 3: Comparative Example 1 was repeated except that 1.0 wt% fumed silica particles functionalized with hexamethyldisilazane (Aerosil RX50 from Evonik, 35±10 μm) were added before the reactor was heated to temperature and the thermoplastic polyurethane particles were added. 2 / g BET surface area and 40 nm average particle size) and 1.0 wt % docusate sodium in combination with polydimethylsiloxane.

[0219] After separation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.15 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 3 at 150X magnification is shown. The average particle size was 51.2 μm and a relatively narrow particle size distribution (span = 0.777) was obtained. The angle of repose was 32.6°. Fig.16 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 3 is shown.

[0220] Example 4: Comparative Example 1 was repeated except that 0.25 wt% fumed silica particles functionalized with hexamethyldisilazane (Aerosil RX50 from Evonik, 35±10 μm) were added before the reactor was heated to temperature and the thermoplastic polyurethane particles were added. 2 / g BET surface area and 40nm average particle size) and 5wt% CALFAX DB-45 (branched C 12Diphenyl oxide disulfonic acid sodium salt, Pilot Chemical) in combination with polydimethylsiloxane.

[0221] After separation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig.17 An exemplary optical microscopic image at 150X magnification is shown of the thermoplastic polyurethane microparticles obtained in Example 4. The average particle size was 121 μm and a relatively narrow particle size distribution (span = 0.435) was obtained. Fig.18A and Fig.18B Exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Example 4 at various magnifications are shown. Fig.19 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 4 is shown.

[0222] Example 5: Comparative Example 1 was repeated except that 1.0 wt% fumed silica particles functionalized with hexamethyldisilazane (Aerosil RX50 from Evonik, 35±10 m 2 / g BET surface area and 40nm average particle size) and 2.5 wt% CALFAX DB-45 (branched C 12 Diphenyl oxide disulfonic acid sodium salt, Pilot Chemical) in combination with polydimethylsiloxane.

[0223] After separation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Fig. 20 An exemplary optical microscopic image of the thermoplastic polyurethane microparticles obtained in Example 5 at 150X magnification is shown. The average particle size was 62.9 μm and a relatively narrow particle size distribution was obtained (span = 0.619). The angle of repose was 31.3°. Fig.21 An exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 5 is shown.

[0224] Comparison of Results: Table 1 below summarizes the formation conditions used for Comparative Examples 1-4 and the properties of the thermoplastic polyurethane microparticles obtained in each case. Table 2 below summarizes the formation conditions used for Examples 1-5 and the properties of the thermoplastic polyurethane microparticles obtained in each case.

[0225] Table 1

[0226]

[0227]

[0228] Table 2

[0229]

[0230]

[0231] As shown in Tables 1 and 2 and the accompanying figures, the combination of silica nanoparticles and sulfonate surfactants effectively forms elastic microparticles with a narrow particle size distribution (span < 0.9) and a sieving yield of greater than 90% of the initial unscreened product (Examples 2-5). In contrast, the sulfate surfactant (Example 1) provides a much wider particle size distribution, albeit with a particle size similar to that of the product prepared with the sulfonate surfactant. The particle size of the elastic microparticles formed in the absence of silica nanoparticles is much larger and the sieving yield is lower (Comparative Examples 1, 3 and 4).

[0232] Fig. 22 Exemplary particle size distribution graphs are shown for Comparative Examples 1 and 4 and Example 3. As shown, the use of silica particles and sulfonate surfactant (Example 3) provides a much smaller particle size distribution.

[0233] Example 5: Selective laser sintering (SLS) was performed using a Snow White SLS printer system (Sharebot). The thermoplastic polyurethane microparticles of Example 3 were deposited in 30 mm x 30 mm squares using the SLS printer system and then sintered under various laser power conditions specified in Table 3 below. The percentage of voids after sintering was calculated using digital microscope software. Little to no agglomeration was observed after sintering, which may indicate good single-layer sintering performance.

[0234] Table 3

[0235]

[0236] 1 Multiply the reported scan rate by 0.04 to obtain the scan rate in mm / s.

[0237] As shown, effective sintering is achieved at laser powers above 20% and up to 45% power (the highest value tested), providing a low porosity material with a small amount of voids, which has less than 1.5% voids at laser powers above 30%. The low void percentage is a characteristic of the thermoplastic polyurethane particles being effectively fused to each other. The powder formation in entry 6 is believed to artificially reduce the amount of voids measured.

[0238] Table 4 compares the laser sintering performance of the thermoplastic polyurethane particles of Example 3 with those of Comparative Example 2 and commercial ADSINT polyurethane particles.

[0239] Table 4

[0240]

[0241] As shown, when the thermoplastic polyurethane particles of Example 3 are used, effective sintering is achieved at laser powers above 20% and up to 45% power (the highest value tested), thereby providing a low porosity material. The laser sintering performance of the thermoplastic polyurethane microparticles of Example 3 is much better than that of the commercial ADSINT thermoplastic polyurethane microparticles, as evaluated by the porosity obtained. The laser sintering performance of the thermoplastic polyurethane microparticles of Example 3 is also better than that of Comparative Example 2 in terms of being sinterable at lower laser powers and providing lower porosity values ​​in most cases. As a representative example, Fig.23 An optical image of the printed product obtained from entry 5 of Table 3 (40% laser power) is shown.

[0242] All documents described herein are incorporated herein by reference for the purpose of all jurisdictions allowing such practice, including any priority documents and / or testing procedures, as long as they do not conflict with this article. As is apparent from the foregoing general description and specific embodiments, although the form of the present disclosure has been shown and described, various modifications may be made without departing from the spirit and scope of the present disclosure. Therefore, the present disclosure is not intended to be limited thereby. For example, the composition described herein may not contain any component or composition that is not explicitly described or disclosed herein. Any method may lack any step that is not described or disclosed herein. Similarly, the term "comprising" is considered to be synonymous with the term "including". Whenever there is a transition phrase "comprising" before a method, composition, element or element group, it should be understood that we also envision that there is a transition phrase "substantially consisting of...", "consisting of...", "selected from..." or "is" before the narration of the composition, element, multiple elements, or the same composition or element group, and vice versa.

[0243] Unless otherwise indicated, all numbers used in this specification and the related claims expressing the number of components, characteristics (such as molecular weight), reaction conditions, etc. should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the following specification and the attached claims are approximate values, which may vary according to the desired characteristics sought to be obtained by the embodiments of the present invention. At a minimum, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted according to the reported significant digits and by applying conventional rounding methods.

[0244] Whenever a numerical range with a lower limit and an upper limit is disclosed, any number and any included range falling within the range are specifically disclosed. Specifically, each value range disclosed herein (in the form of "about a to about b", or equivalently, "about a to b", or equivalently, "about ab") should be understood to set forth each value and range covered within the wider value range. In addition, the terms in the claims have their ordinary, common meanings unless otherwise explicitly and clearly defined by the patentee. In addition, the indefinite articles "a" or "an" used in the claims are defined herein to mean that there is one or more than one of the elements introduced therein.

[0245] One or more exemplary embodiments are presented herein. For the sake of clarity, all features of physical implementation are not described or shown in this application. It should be understood that in the development of the physical implementation of the present disclosure, many specific decisions must be made to achieve the goal of the developer, such as meeting system-related constraints, business-related constraints, government-related constraints and other constraints, which vary and change over time due to implementation. Although the efforts made by the developer may be time-consuming, such efforts will be a routine task for those of ordinary skill in the art who benefit from the present disclosure.

[0246] Therefore, the present disclosure is well suited to achieve the goals and advantages mentioned, as well as those inherent therein. The specific embodiments disclosed above are merely exemplary, as the present disclosure may be modified and implemented in different but equivalent ways apparent to one of ordinary skill in the art having the benefit of the teachings herein. In addition, no limitations are contemplated on the details of construction or design shown herein, except as described in the following claims. Therefore, it is apparent that the specific exemplary embodiments disclosed above may be altered, combined or modified, and all such variations are considered to be within the scope and spirit of the present disclosure. The embodiments exemplarily disclosed herein may be appropriately implemented in the absence of any element not specifically disclosed herein and / or any optional element disclosed herein.

Claims

1. A composition comprising: a plurality of elastomeric particles, the plurality of elastomeric particles comprising a polyurethane polymer and a plurality of nanoparticles, the polyurethane polymer defining a core and an outer surface of the elastomeric particles, and the plurality of nanoparticles associated with the outer surface; wherein the elastic particles have a D50 in the range of 1 μm to 130 μm with a size span of 0.9 or less, The composition further comprises a sulfonate surfactant.

2. The composition of claim 1, wherein the plurality of nanoparticles comprises a plurality of oxide nanoparticles.

3. The composition of claim 1, wherein the plurality of nanoparticles consists essentially of a plurality of oxide nanoparticles.

4. The composition of claim 2, wherein the plurality of oxide nanoparticles comprises silicon dioxide nanoparticles.

5. The composition of claim 2, wherein the plurality of oxide nanoparticles consists essentially of silicon dioxide nanoparticles.

6. The composition of claim 4, wherein the silica nanoparticles have a D50 in the range of 5 nm to 50 nm.

7. The composition of claim 1, wherein at least a portion of the sulfonate surfactant is associated with the outer surface.

8. The composition of claim 1, wherein at least a majority of the plurality of elastic microparticles are substantially spherical in shape.

9. The composition of claim 1, wherein the plurality of nanoparticles are at least partially embedded within the outer surface.

10. A three-dimensional printing method, the method comprising: depositing the composition according to claim 1 in a specified shape; as well as Once deposited, heating at least a portion of the elastomeric particles to promote consolidation of the elastomeric particles and form a consolidated body; The consolidated body is formed layer by layer and has a porosity of 3.5% or less after consolidation.

11. The method of claim 10, wherein the composition is deposited and the elastic particles are consolidated using a three-dimensional printing device.

12. The method of claim 10, wherein the plurality of nanoparticles remain associated with the consolidated body. The method of claim 10 , wherein the plurality of nanoparticles comprises a plurality of oxide nanoparticles.

14. The method of claim 10, wherein the plurality of nanoparticles consists essentially of a plurality of oxide nanoparticles. The method of claim 13 , wherein the plurality of oxide nanoparticles comprises silicon dioxide nanoparticles.

16. The method of claim 13, wherein the plurality of oxide nanoparticles consists essentially of silicon dioxide nanoparticles.

17. The method of claim 10, wherein the elastomeric microparticles further comprise a sulfonate surfactant.

18. The method of claim 17, wherein at least a portion of the sulfonate surfactant is associated with the outer surface.

19. A method of forming elastic microparticles using melt emulsification, the method comprising: combining the polyurethane polymer, sulfonate surfactant, and nanoparticles with a carrier fluid at a heated temperature at or above the melting point or softening temperature of the polyurethane polymer; wherein the polyurethane polymer and the carrier fluid are substantially immiscible at the heated temperature; applying sufficient shear at the heated temperature in the presence of the sulfonate surfactant and the nanoparticles to disperse the polyurethane polymer in the carrier fluid as liquefied droplets; After the liquefied droplets have been formed, cooling the carrier fluid to at least a temperature at which an elastomeric particle is in the form of a solidified state, the elastomeric particle comprising a polyurethane polymer and a plurality of the nanoparticles, the polyurethane polymer defining a core and an outer surface of the elastomeric particle and the plurality of nanoparticles associated with the outer surface; wherein the elastic microparticles have a D50 in the range of 1 μm to 130 μm, with a size span of 0.9 or less; as well as The elastic particles are separated from the carrier fluid.

20. The method of claim 19, wherein the plurality of nanoparticles comprises a plurality of oxide nanoparticles.

21. The method of claim 19, wherein the plurality of nanoparticles consists essentially of a plurality of oxide nanoparticles.

22. The method of claim 20, wherein the plurality of oxide nanoparticles comprises silicon dioxide nanoparticles.

23. The method of claim 20, wherein the plurality of oxide nanoparticles consists essentially of silicon dioxide nanoparticles.

24. The method of claim 19, wherein the carrier fluid comprises silicone oil.

25. The method of claim 19, wherein at least a portion of the sulfonate surfactant is associated with the plurality of elastomeric microparticles.

26. The method of claim 25, wherein at least a portion of the sulfonate surfactant is associated with the outer surface.

27. The method of claim 19, wherein the plurality of nanoparticles are at least partially embedded within the outer surface.

Citation Information

Patent Citations

  • Powdery composition comprising thermoplastic polyurethane and use thereof

    US20150152214A1

  • Use of thermoplastic polyurethane powders

    US20170129177A1

  • Method of producing fine particles of thermoplastic resin

    US4863646A

  • Polyurethane Microspheres

    US5859075A

  • Methods of using thermoplastic polyurethanes in selective laser sintering and systems and articles thereof

    WO2015109143A1